Cancellation of singularities of RRRRP planar parallel robots - ÖZDEMİR, MUSTAFA (My University, 2022)
Parallel robots have many advantages compared to their conventional serial counterparts such as high accuracy and precision, high rigidity, low energy consumption and high payload carrying capacity. Their major disadvantage, however, is the existence of Type II singularities within the workspace. When approaching to these singularities, the magnitudes of the Lagrange multipliers and of the actuator forces and/or torques go to infinity, and hence controllability of the robot is lost. This paper studies conditions for cancellation of Type II singularities of the RRRRP-type planar parallel robot from its dynamic model. The RRRRP robot belongs to the five-bar parallel robot family. Keywords: Parallel robot, Planar parallel robot, Singularity, Singularity cancellation
Keywords: Parallel robot; Planar parallel robot; Singularity; Singularity cancellation